ANALISIS PENERAPAN APLIKASI E-RAPOR PADA SMPN 1 JEUMPA ACEH BARAT DAYA - edi hasri (JINTECH: Journal Of Information Technology, 2021)
The E-Rapor application is designed to facilitate the preparation of competency achievement reports and data processing in order to see the achievement of student learning outcomes carried out by subject teachers. This study applies a quantitative model to the teacher's level of understanding testing. The sample of this study was 20 subject teachers at SMPN 1 Jeumpa Aceh Barat Daya. With the answers generated from the data, respondents have an average score of 74.8 with a percentage of 62-81% so that the use of the E-Report Application at SMPN 1 Jeumpa Aceh Barat Daya lies in the agree category. The significance value obtained is 0.152 > 0.05, it can be concluded that Ha is rejected and Ho is accepted. Based on the Anova table, it also shows a value of 2.263 > 4.49 with the result that there is an effect, so the conclusion is that in terms of teacher use and understanding of the use of the E-Rapor Application at SMPN 1 Jeumpa Aceh Barat Daya there is no significant effect.